Advances in CAR-T cell therapy for hematologic and solid malignancies: latest updates from 2024 ESMO Congress - Huageng Huang; Le Yu; Huawei Weng; Wei Zhang; Zhao Wang; Lin Wang; He Huang (Journal of Hematology & Oncology)
Abstract Chimeric antigen receptor (CAR)-T cell therapy has emerged as one of the most rapidly evolving modalities of immunotherapy, with substantial success in the treatment of hematological malignancies and encouraging outcomes in solid tumors. Yet, the efficacy of CAR-T therapy is hindered by challenges such as suboptimal expansion and persistence, adverse events, a scarcity of ideal targets, high immunosuppression, and insufficient infiltration due to the intricate tumor microenvironment, all of which limit its application. The 2024 European Society for Medical Oncology (ESMO) Congress presented novel CAR-T cell therapies for hematologic and solid malignancies, focusing on strategies such as cytokine modulation, innovative targets, allogeneic development, mRNA vaccine synergy, in vivo delivery and conditional activation to surmount these challenges.